Pemodelan Regresi Data Panel Pada Indeks Pembangunan Manusia di Pulau Sumatera - Muhayratu Farisha; Ulkya Maisarah; Hezron Paul Marpaung; Asnidar Asnidar; Ahmad Ridha (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2024)
The island of Sumatra has 10 provinces with a Human Development Index level that is not much different from the national Human Development Index, several provinces on the island of Sumatra have a Human Development Index below the national Human Development Index. The aim of this research is to analyze the Human Development Index and the factors that influence it in Sumatra for the 2018-2022 period. This research is quantitative research. The variables used in this research are the Human Development Index, Gross regional domestic product, Economic Growth, Poverty, and the Gini Index. The panel data method is used for analysis in the form of cross section data from 10 provinces on the island of Sumatra and time series data for 2018-2022. The results of this research show that Gross regional Domestic Product and Economic Growth have a negative and insignificant effect on the Human Development Index, Poverty and the Gini Index have a negative and significant effect on the Human Development Index in Sumatra for the 2018-2022 period.